Implementation of Curriculum in Vocational High Schools in Indonesia Based on Organizational Citizenship Behavior - Soeprijanto, Soeprijanto; Prihantoro, C. Rudy; Priyanto, Sugeng (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This study aims to analyze the factors significantly affecting the implementation of the vocational high school curriculum in Indonesia based on Organizational Citizenship Behavior. This study used survey methods with a quantitative approach. Data were obtained from Vocational High School teachers in Indonesia, with 292 respondents representing 30 provinces from 34 provinces. The independent variables were transformational leadership and organizational climate. Meanwhile, the dependent variable was Organizational Citizenship Behavior, and the intermediate variables were motivation and job satisfaction. The data analysis technique used in this study was Structural Equation Modelling. Two conclusions can be drawn from this study. First, there is the effect of applying OCB in educational organizations, especially in implementing curriculum in VHS. Second, leadership and organizational climate directly affect the application of OCB in the school environment. A conducive and accommodative school organizational climate was indirectly affected by the transformational leadership style to create an organizational climate conducive and accommodative for individual teachers in optimally implementing curriculum in VHS in Indonesia.